Beachrock formation mechanism through minerochemical analysis and cement characteristics. Case study W. Akrotiri Peninsula, Cyprus - Saitis, G.; Polidorou, M.; Evelpidou, N. (RCG2019 “Geomorphology of Climatically and Tectonically Sensitive Areas”, 2019)
Beachrocks are hard coastal sedimentary formations consisted from various beach sediments, coastal fauna residues and anthropogenic articles. Beachrocks are rapidly cemented through precipitation of carbonate cements typically consisted of High-Magnesian Calcite (HMC), which commonly precipitates in shallow marine environments, (>4 mol % CaCO3 or 1.2 wt. %) or aragonite (Ar). However, debate still exists concerning the accurate depositional environment of beachrocks and data for the mechanism of their formation are considered necessary. This study aims to contribute to the understanding of the beachrock formation, using mineralogical and geochemical methods, analyzing the cement and the consolidated sediments. Bulk samples were collected from three consecutive beaches located at the West part of Akrotiri Peninsula (Cyprus island). The samples were examined under polarizing microscope for the determination of the cement (HMC as micritic and sparitic crystals), its characteristics (isopachous bladed coating, formation of meniscus etc) and the participation of well-preserved fossil fragments. The mineralogical analysis, with the use of XRD analyzer, indicated a variety of minerals which consisting the beachrock (quartz, carbonates, plagioclase, olivine, biotite, zircon etc). Using SEM-EDS it was possible to accurately determine the cement composition and to observe its crystal characteristics. The cement agent was mainly consisted by High-Magnesian Calcite (HMC) of different crystal sizes and matrix material was present as secondary pores filling. The three studied beachrocks at the west of Akrotiri peninsula, were formed in the middle-low intertidal zone. Evidence of continuous uplift of the beachrock is observed both from geomorphological analysis and through its infrastructure. The beachrocks were highly affected by the nearby Kouris river, which supplied the material derived from the inner Cyprus areas rich in Mg2+ rocks (eg. ophiolites) and Ca2+ (eg. limestones, marbles).